ANALISIS SYSTEM ANTRIAN TERHADAP KEPUASAN PELANGGAN PADA PT. BANK NEGARA INDONESIA (PERSERO) TBK. KANTOR CABANG PEMBANTU AMPERA PALEMBANG - Liliana .; M. Dede Pitanda (JURNAL KOMPETITIF, 2017)
This research basically discusses how PT Bank Negara Indonesia (Persero) Tbk. Branch Office Ampera Palembang in addressing the frequent accumulation of queue is quite a lot and customers need a long time to wait for turn to get service at PT Bank Negara Indonesia (Pesero) Tbk. Branch Office Ampera Palembang. Therefore, the purpose of this research is to know the performance of queue sistrem currently applied to PT Bank Negara Indonesia (Pesero) Tbk. Palembang Ampera Helper Branch Office.Based on the research results, the M / M / S (Multiple Channel Query System) model established by PT Bank Negara Indonesia (Pesero) Tbk. Branch Office Ampera Palembang is good because the longest time required by a customer in the queue for only 2.2366 minutes and the longest queue only as much as 2.3875 people and this occurs only in the period of time at 10:00 to 11:00 every day.But sometimes at certain times there are only three tellers that operate because there is one teller that is used to serve customers who will pay taxes and salary and special salary this channel does not use a queue card. This has resulted in an increase in the average number of customers queuing over the 10.00 - 11.00 period as much as 10,5215 customers. This can be proven based on the above calculation that during the peak hours of 10:00 to 11:00 the number of customers who queue as much as 2.3857 and when there is the assignment of one person teller then the customer queuing up to 12,9027, and an increase in the average amount of time required by customers in The previous queue is 2.2366 menint to 12,1005. Therefore PT. Bank Negara Indonesia (Pesero) Tbk. Branch Office Ampera Palembang needs to consider the arrival rate of customers and the level of queues that occur every day, so that the operational performance of PT Bank Negara Indonesia (Pesero) Tbk. Branch Office Ampera Palembang as a whole is not disturbed and the transaction process can run optimally so as not to make the customer queuing for too long in the transaction.Keywords: Customer Satisfaction